2015
DOI: 10.1007/s10654-014-9984-2
|View full text |Cite
|
Sign up to set email alerts
|

The global impact of non-communicable diseases on healthcare spending and national income: a systematic review

Abstract: The impact of non-communicable diseases (NCDs) in populations extends beyond ill-health and mortality with large financial consequences. To systematically review and meta-analyze studies evaluating the impact of NCDs (including coronary heart disease, stroke, type 2 diabetes mellitus, cancer (lung, colon, cervical and breast), chronic obstructive pulmonary disease and chronic kidney disease) at the macro-economic level: healthcare spending and national income. Medical databases (Medline, Embase and Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
191
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(205 citation statements)
references
References 163 publications
1
191
0
13
Order By: Relevance
“…Most such diseases are chronic, require health delivery infrastructure and skilled workforces, and are costly to treat. 27 For example, a recent study in Tanzania revealed that noncommunicable diseases were responsible for only 27 percent of the country's health burden but for nearly half of its hospital admissions and hospitalization days. 28 Studies conducted in the United States and New Zealand showed higher rates of inpatient surgical procedures for the treatment of noncommunicable diseases than for that of communicable, maternal, and neonatal diseases (34 percent versus 24 percent in the United States and 32 percent versus 16 percent in New Zealand).…”
mentioning
confidence: 99%
“…Most such diseases are chronic, require health delivery infrastructure and skilled workforces, and are costly to treat. 27 For example, a recent study in Tanzania revealed that noncommunicable diseases were responsible for only 27 percent of the country's health burden but for nearly half of its hospital admissions and hospitalization days. 28 Studies conducted in the United States and New Zealand showed higher rates of inpatient surgical procedures for the treatment of noncommunicable diseases than for that of communicable, maternal, and neonatal diseases (34 percent versus 24 percent in the United States and 32 percent versus 16 percent in New Zealand).…”
mentioning
confidence: 99%
“…Healthcare costs are rising at a much faster rate than gross domestic product (GDP), creating budget deficiencies [5]. This reinforces payers to ensure that they put money in treatments that are cost effective, add value to patients and improve population health.…”
Section: Why Rwe Now?mentioning
confidence: 99%
“…Parallel to this, global public health trends show increasing burden of noncommunicable diseases due to unhealthy lifestyle [5], implying a large proportion of people living a long unhealthy life about 30-40 years.…”
Section: Why Rwe Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their chronicity, these diseases place an increased demand on the healthcare sector, with an increasing number of persons requiring specialised care. In addition, the fact that many of those affected by CNCD are of working-age, affects the country's economic growth through productivity losses and prolonged disability (Ezzati & Riboli, 2012;Muka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%